Rich Task Construction: Making "Good" Problems Better - Waters, Michael (Ohio Journal of School Mathematics, 2018)
The author describes characteristics of rich problems and provides mathematics teachers with strategies for transforming routine exercises into problems that promote problem-solving practices with a focus on problems for which a solution is not immediately apparent. Several problems and solutions are presented with a mindful approach to assigning problems.